2018
DOI: 10.1088/1612-202x/aaf178
|View full text |Cite
|
Sign up to set email alerts
|

Label-free detection of brain invasion in meningiomas by multiphoton microscopy

Abstract: Brain invasion in meningiomas relates to the poor prognosis. Therefore, accurate detection and treatment of brain invasion are of particular importance. In this study, multiphoton microscopy (MPM) was introduced for label-free detection of brain invasion in meningiomas by the combination of the two-photon excited fluorescence imaging, second-harmonic generation imaging and spectral imaging. Results show that MPM has the ability to morphologically and spectrally identify brain invasion in meningiomas. What is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…MPM has advantages of increasing the imaging depth, reducing phototoxicity and photobleaching , and the ability to generate pathology‐like images based on the natural intrinsic fluorescence properties of tissues. It has been widely used in cancer research and diagnosis, such as brain cancer , breast cancer , and esophageal cancer . In 2011, Tewari et al employed MPM to identify relevant prostatic and periprostatic structures in prostate cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…MPM has advantages of increasing the imaging depth, reducing phototoxicity and photobleaching , and the ability to generate pathology‐like images based on the natural intrinsic fluorescence properties of tissues. It has been widely used in cancer research and diagnosis, such as brain cancer , breast cancer , and esophageal cancer . In 2011, Tewari et al employed MPM to identify relevant prostatic and periprostatic structures in prostate cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The features they used were different water molecule diffusion motion speeds and ranges in magnetic resonance diffusion-weighted imaging than margins. Huang et al analyzed the factors of tumor irregular shape and blurred borders as significantly associated with pathological invasion (24), and other studies have shown changes in the microenvironment during brain tumor infiltration (25). In Table 3, it is shown that the correlation between MSC values and invasion distance of gliomas is higher than other multifactorial pathologic invasion characteristics through Spearman's correlation coefficient of actual invasion distance and MSC; the average correlation coefficient between actual invasion distance and MSC reached −0.631, which is a strong correlation.…”
Section: Discussionmentioning
confidence: 99%